Varying chiral ratio of pinic acid enantiomers above the Amazon rainforest - D. Leppla; N. Zannoni; L. Kremper; J. Williams; C. Pöhlker; M. Sá; M. C. Solci; T. Hoffmann (Atmospheric Chemistry and Physics, 2023)
Chiral chemodiversity plays a crucial role in biochemical processes such as insect and plant communication. However, the vast majority of organic aerosol studies do not distinguish between enantiomeric compounds in the particle phase. Here we report chirally specified measurements of secondary organic aerosol (SOA) at the Amazon Tall Tower Observatory (ATTO) at different altitudes during three measurement campaigns at different seasons. Analysis of filter samples by liquid chromatography coupled to mass spectrometry (LC-MS) has shown that the chiral ratio of pinic acid (C9H14O4) varies with increasing height above the canopy. A similar trend was recently observed for the gas-phase precursor α-pinene but more pronounced. Nevertheless, the measurements indicate that neither the oxidation of (+/−)-α-pinene nor the incorporation of the products into the particulate phase proceeds with stereo preference and that the chiral information of the precursor molecule is merely transferred to the low-volatility product. The observation of the weaker height gradient of the present enantiomers in the particle phase at the observation site can be explained by the significant differences in the atmospheric lifetimes of reactant and product. Therefore, it is suggested that the chiral ratio of pinic acid is mainly determined by large-scale emission processes of the two precursors, while meteorological, chemical, or physicochemical processes do not play a particular role. Characteristic emissions of the chiral aerosol precursors from different forest ecosystems, in some cases even with contributions from forest-related fauna, could thus provide large-scale information on the different contributions to biogenic secondary aerosols via the analytics of the chiral particle-bound degradation products.